A tradição dinâmica: o transbordamento como estratégia do papa Francisco para ultrapassar a polarização entre o depósito da fé e da vida. - Marquim, Gabriel Nogueira Linhares (2023)
This thesis presents the inductive model developed by Pope Francis – called dynamic tradition by him – to deal with the tension present in the contemporary religious phenomenon, marked by the opposition between the maintenance of tradition and the need for renewal, which has generated polarized movements, between fundamentalisms and relativisms. Based on a bibliographical review, we demonstrate how differentiation and ambivalence, characteristics contained in the West's modernization project, frayed in a polarization that is ever more present in different areas, such as politics and culture. But also in the religious context, when opposing groups intend the relationship between tradition and renewal in their faith contexts, making an alternative to this dichotomy necessary. For this, we firstly situate how the biographical trajectory of Jorge Mario Bergoglio presents facts that made him deal with polarizing events, and how his intellectual thought was forged from influences that go beyond this tension. From a theoretical-methodological point of view, we mobilize some more important concepts, such as modernity, from Jürgen Habermas; religion, through Peter Berger; habitus, field and strategy, according to Pierre Bourdieu's praxeology. Finally, we highlight the strategy Francis uses to overcome – by overflow – what he understands as the relationship between the deposit of faith and life: a dynamic tradition. Capable of finding and resuming the core of faith, making it relate and give new responses to the contingencies and challenges of human reality.